Pharmacoscintigraphy: Advancing Nanotheranostic Development Through Radionuclide Imaging - María Jimena Salgueiro; Marcela Analia Moretton; Vanina Medina; Diego Chiappetta; Marcela Zubillaga (Journal of Nanotheranostics)
Pharmacoscintigraphy has emerged as an essential tool in the research and development of nanomedicines, particularly in the field of nanotheranostics. By enabling the real-time, non-invasive tracking of their biodistribution, pharmacokinetics, and therapeutic efficacy, these imaging techniques provide invaluable insights that drive the optimization of nanomedicine formulations. The integration of gamma scintigraphy, SPECT, and PET imaging has significantly enhanced our understanding of nanocarrier behavior, supporting their clinical translation by ensuring precise targeting, minimizing off-target effects, and improving therapeutic outcomes. Future advancements in hybrid imaging modalities, novel radionuclide tracers, and personalized imaging-guided therapies will further expand the impact of pharmacoscintigraphy in nanomedicine. Additionally, the increasing recognition of imaging-based validation in regulatory approval processes underscores the growing importance of these techniques in drug development. As nanotheranostics continues to evolve, radionuclide imaging will remain a pivotal component in their preclinical and clinical evaluation, facilitating safer and more effective precision medicine approaches.